Second-step lectotypification of four names in the genus Burmannia (Burmanniaceae) - Arunraj, Parappurakkal Thazhe; Sanjai, Viswanathamandiram Natarajakaimal (Phytotaxa, 2023)
Here we discuss the second-step lectotypification of four names in the genus Burmannia L. viz. B. cochinchinensis Gagnep., B. letestui Schltr., B. subcoelestis Gagnep., and B. tisserantii Schltr.